Analysis of Road Network Performance in Universitas Islam Negeri Raden Intan Area using Microsimulation PTV VISSIM - Michael Michael; Frenda Syaputra; Bernaditha Catur Marina; Ayu Kamila Khanza (Universitas Islam Raden Rahmat, Malang, 2025)
The road network in the area of the Raden Intan State Islamic University in Lampung often experiences congestion due to heavy traffic, resulting in a decline in road performance. The objective of this study is to analyze existing performance, implement improvement scenarios, and evaluate the impact of improvement scenarios. A descriptive quantitative method was used, involving field surveys covering traffic volume, vehicle speed, and side obstacles. Traffic simulation modeling was conducted using PTV VISSIM software, calibrated by adjusting microscopic traffic parameters and validated through GEH and MAPE tests, ensuring the modeling results accurately represent actual traffic conditions on-site. The results showed the performance of the existing road network, with an average speed of 25.13 km/h, an average queue length of 16.3 m, and an average delay of 73.84 seconds. Three improvement scenarios were conducted using a one-way system and the use of the right lane. All three improvement scenarios showed improvements, with the most significant improvement using scenario 1, which had an average speed of 26.69 km/h, an average queue length of 2.18 m, and an average delay time of 10.13 seconds.